Depression behavior and mechanism of pyrogallol on bismuthinite flotation. (25th January 2021) - Lin, Shangyong; He, Jianyong; Liu, Runqing; Hu, Yuehua; Sun, Wei
Abstract: Pyrogallol, an eco-friendly derivative of tannic, was a potential substitute of toxic depressant used in bismuth-molybdenum (Bi–Mo) sulfide ore flotation. However, unclear depression mechanisms of pyrogallol on bismuth sulfides hindered its further application in the industry. In this work, the effect of pyrogallol on the flotation performance of bismuthinite was evaluated using flotation tests, and associated interaction mechanisms were investigated by using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT) calculations. Micro-flotation tests showed that pyrogallol exhibited excellent depressing performance to bismuthinite in the whole pH range tested (2–12). In the presence of 300 g/t pyrogallol, over 95% of bismuthinite was effectively depressed in the real flotation process at pH around 9. FTIR and XPS results demonstrated that pyrogallol was chemisorbed on bismuthinite through the interactions among Bi atoms exposed on the bismuthinite surface and O−H groups in pyrogallol. The adsorption mechanism was further ascertained by DFT calculations, which revealed that the Bi–O–C single bond and the five-membered ring complex models were involved in the chemisorption of pyrogallol on bismuthinite surface. The work presented here not only provides new insights into the inhibition mechanisms of pyrogallol on bismuthinite but also provides theoretical support for the industrial application of pyrogallol. Graphical abstract: Image 1 Highlights: The floatability of bismuthinite decreases with increasing pH. Pyrogallol exhibits excellent depression effect on bismuthinite flotation. Bi sites in bismuthinite surface account for pyrogallic acid adsorption. Pyrogallol chemisorbs on bismuthinite surface via the formation of Bi–O–C bonds.